Leishmania donovani Induced Cutaneous Leishmaniasis: An Insight into Atypical Clinical Variants in Sri Lanka. (27th May 2019) - Siriwardana, Yamuna; Deepachandi, Bhagya; Gunasekara, Chalukya; Warnasooriya, Wipula; Karunaweera, Nadira D.
Abstract : Sri Lanka is a recent focus having Leishmania donovani induced cutaneous leishmaniasis (CL) as the main clinical entity. A separate clinical entity within profile of CL was described in this study. Laboratory confirmed cases of CL (n= 950, 2002-2014) were analysed. Most lesions showed known classical developmental stages of CL (CCL) observed in other CL endemic settings while few cases (13%, 122/950) showed atypical skin manifestations (ACL). Clinical, geographical, and treatment response patterns of ACL were different from those of CCL. ACL was mainly found among males (68.0%), in 21-40 year age group (51.6%), and reported delayed treatment seeking (23.5% vs 16.3% in CCL), more nonclassical onset (lesions other than acne form <1cm sized papules), (12.1 vs 2.7%, P<0.05.), more head and neck lesions (41.5%. vs 27.2%), more large lesions (>4cm), (18.6 vs 9.9%), and poor laboratory positivity rates (65.6% vs 88.2%) when compared to CCL. When compared to lesions reporting a typical onset, lesions reporting nonclassical onset were more likely to develop ACL later on (50.1% vs 10.7%). As compared to lesions on limbs, those on head and neck and trunk were more likely to be ACL (7.0%, 16.3%, and 22.8%, respectively, P<0.05). ACL features were not age or gender dependent. Highest proportion within ACL category (32.8%) and small proportion of CCL (10.1%) originated from less leishmaniasis prevalent areas (other regions) (P<0.05). North reported more ACL than South (15.9% vs 7.4%). A total of 95 CL cases with a significant travel history were further analyzed. Residents of other regions when acquired infection from North or South developed more ACL than residents in North or South (60.9% vs 15.9% and 42.9% vs 7.4% respectively). Patients in other regions when travelled to North developed more ACL than when they travelled to South (60.9%, 42.9%). ACL and CCL required an average of 18 doses over 16.7 months and 10 doses over 12 weeks, respectively, to achieve a complete clinical cure. Underlying host immunological factors, parasite strain variations and regional variations of both could be underlying etiologies. Established independent transmission within less leishmaniasis prevalent regions combined with an unusual clinical picture leading to poor clinical suspicion and low laboratory confirmation rate will pose potential difficulties in early case detection in these highly populated and commercialized areas. This in turn will further facilitate silent and high disease transmission.